Molecular Approaches for Breeding Abiotic Stress Tolerance Traits in Capsicum Species - Momo, J.; Islam, K.; Kumar, N.; Ramchiary, N.
Capsicum is an important member of the Solanaceae family grown worldwide for its fruits which are utilized as spice as well as a vegetable crop. Capsicum fruits are highly rich in pharmacological compounds such as carotenoids (provitamin A), vitamin C and E, flavonoids and the distinct metabolite alkaloid complex known as capsaicinoids which impart pungency to its fruits. Like other crop plants, Capsicum suffers major yield losses and quality setbacks due to adverse abiotic conditions such as drought, salinity, extremely high and low temperatures and humidity. These environmental constraints limit the productivity and affect the physiological growth of Capsicum by altering osmotic balance, affecting growth, reproduction, fruit ripening and quality. Therefore, Capsicum needs urgent attention from the plant researchers and breeders in order to reduce losses due to environmental conditions. In this chapter, we review the current state of abiotic stress tolerance in Capsicum spp. expanding over the natural germplasm, molecular breeding and resistance mechanisms. Marker-assisted selection and genome-wide association studies for the useful exploitation of resistance genes and QTLs have offered considerable advantages over the conventional plant breeding approaches for the improvement of Capsicum in terms of accuracy, specificity and duration. Furthermore, the next-generation sequencing technologies have proven breakthroughs in the field of identification of the genomic regions responsible for stress tolerance, evasion and responses which could be employed for future Capsicum breeding programs.
Keywords: CAPSICUM; DROUGHT; SALINITY; HEAT; HUMIDITY; RESISTANCE GENES